2020
DOI: 10.3390/jcm9061666
|View full text |Cite
|
Sign up to set email alerts
|

EUS-Guided Versus Percutaneous Celiac Neurolysis for the Management of Intractable Pain Due to Unresectable Pancreatic Cancer: A Randomized Clinical Trial

Abstract: Although endoscopic ultrasound-guided celiac neurolysis (EUS-CN) and percutaneous celiac neurolysis (PCN) are utilized to manage intractable pain in pancreatic cancer patients, no direct comparison has been made between the two methods. We compared the efficacy and safety of EUS-CN and PCN in managing intractable pain in such patients. Sixty pancreatic cancer patients with intractable pain were randomly assigned to EUS-CN (n = 30) or PCN (n = 30). The primary outcomes were pain reduction in numerical rating sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…An initial search identified 176 articles, out of which 142 studies were initially excluded (studies that involved chronic pancreatitis patients and studies presented as abstracts in conferences). Thirty-four relevant studies were selected and reviewed in detail, of which 18 studies that utilized celiac plexus block technique were excluded and only 16 studies met the final inclusion criteria [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Figure 1 shows the search results.…”
Section: Resultsmentioning
confidence: 99%
“…An initial search identified 176 articles, out of which 142 studies were initially excluded (studies that involved chronic pancreatitis patients and studies presented as abstracts in conferences). Thirty-four relevant studies were selected and reviewed in detail, of which 18 studies that utilized celiac plexus block technique were excluded and only 16 studies met the final inclusion criteria [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Figure 1 shows the search results.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the benefit of NCPB by comparing it with standard systemic medical therapy; NCPB can provide analgesia more effectively and lead to a reduction in the use of opioids and their related side effects [ 8 , 11 , 17 , 23 - 26 ]. Wong et al [ 8 ] demonstrated that NCPB could provide more effective analgesia than a sham block and systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For the transdiscal approach, a virtual transdiscal needle pathway was drawn and the oblique angle from the axis was measured in advance, using the most recent abdominal computed tomographic (CT) image before the procedure [ 17 , 18 ]. After positioning the needle obliquely to an angle measured from the anteroposterior view under fluoroscopic guidance, local skin infiltration was performed with 2% lidocaine.…”
Section: Methodsmentioning
confidence: 99%
“…The percutaneous group showed a slightly favorable reduction in back pain as compared to the endoscopic USG group but no reduction in opioid consumption was seen in either group. The results demonstrated that both techniques are safe, effective and should be utilized according to the expertise and resources available at each facility (24). Neurolytic celiac plexus block has been found to be very effective in pain control in pancreatic cancer patients especially if performed early in the course of the disease.…”
Section: Evidencementioning
confidence: 94%